Formulation of fortified media consisting of oil palm empty fruit bunch biocompost and oil palm kernel shell biochar for the enhancement of bioactive compounds in centella asiatica (L.) urban - Abu Bakar, Izza Nadira; Ibrahim, Mohamad Faizal; Hakiman, Mansor; Jenol, Mohd Azwan; Zainal, Nahrul Hayawin; Abd-Aziz, Suraini; Prasongsuk, Sehanat (Lembaga Minyak Sawit Malaysia, 2025)
Centella asiatica, commonly known as Pegaga, is renowned in Malaysia for its abundant bioactive compound content, making it a highly valued herb. These bioactive compounds, including phenolics, antioxidants, and triterpenes, possess pharmacological activities that are beneficial for health. To optimise the properties of these bioactive compounds, Pegaga Kampung, a superior variety of C. asiatica in Malaysia, was cultivated in 14 different formulations of fortified media. The fortified media were formulated by incorporating various ratios of oil palm empty fruit bunch (OPEFB) biocompost, oil palm kernel shell (OPKS) biochar, organic fertiliser, inorganic fertiliser and soils. Our findings showed that fortified media with a high biocompost ratio of 25:75 (soil:biocompost) and enriched with inorganic fertiliser had a 33% enhanced total phenolic content (TPC). The combination of soil, biocompost and biochar at a ratio of 50:25:25, enriched with organic fertiliser, was found to increase the TPC by 30% and the antioxidant properties by 16% compared to cultivation in soil alone (control). This suggested that the use of fortified media containing OPEFB biocompost and OPKS biochar, along with organic or inorganic fertilisers, significantly improves the bioactive compound characteristics of C. asiatica.